Women: their husbands, their careers and their families - Ruddick, Lindsay (Kansas State University, 2007)
Gender is a constructing concept around which the traditionally structured marriage was formed. An undercurrent of traditional thought still influences how women make their decisions around pursuing a career and caring for their children. Their relationships with their husbands, in part influences both their decision-making and experience of their roles. This was a qualitative multiple care study describing women's decision-making around and their experiences of these roles. Themes found in the participant's narratives related to finances, intentional decision-making, and the fluidity of child-care and work roles. Final reflections during the child launching phase of life showed that role congruency was important for the participants and that they were currently satisfied with their situations.
Keywords: Women; Careers; Roles; Childcare; Home Economics (0386)